PENERAPAN TERAPI RELAKSASI FOOT MASSAGE DAN AROMATERAPI LAVENDER TERHADAP PENURUNAN TINGKAT KELETIHAN PADA ANAK DENGAN CHRONIC KIDNEY DISEASE - Nanda Mutiara Sholikhah; Armenia Diahsari; Dwi Prasetyorini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Small vessel vasculitis (SVV) is a group of autoimmune diseases affecting small blood vessels that can lead to serious complications, often requiring hospitalization in pediatric patients. However, hospitalization can trigger anxiety, pain, and psychological regression in children. Play therapy is one non-pharmacological intervention to reduce anxiety related to hospital care. The aim of this study was to determine the effect of play therapy on reducing anxiety levels in children with small vessel vasculitis in the West Aster Ward of Dr. Sardjito General Hospital. This study used a qualitative descriptive case study design on a 13-month-old child diagnosed with small vessel vasculitis. Data were collected through interviews with parents, observation, and medical records. The intervention was carried out for 4 days with a duration of ±15 minutes per session, including hand puppet play therapy and nursing interventions according to the identified diagnoses. The results of this study showed that the patient presented with main symptoms of pain, anxiety, and ineffective peripheral perfusion. The initial anxiety score based on the anxiety rating scale was 6, and after the application of puppet play therapy, it decreased to 5. Although implementation was temporarily hindered by severe pain (FLACC 8–9), play therapy still had a positive effect on reducing anxiety, even though it was not fully resolved. In conclusion, puppet play therapy in children with small vessel vasculitis has been shown to help reduce anxiety levels during hospitalization. However, the success of the intervention is influenced by physiological factors such as pain, clinical condition, and the therapeutic relationship between nurses, patients, and families.